Editorial: Teachers’ work in Aotearoa New Zealand’s changing policyscape - Helena Cook; Christoph Teschers; Nesta Devine; Daniel Couch; Kay-Lee Jones (New Zealand Journal of Teachers' Work)
It is not easy to be an educator in 2025 in Aotearoa New Zealand. Amidst a variety of pressures, many educators continue to see their role as not merely a job but rather a privilege to guide, support, and empower future generations. However, while teaching is never ‘easy’, it seems that attacks on education, educators, and widely shared values in education such as equity, fairness, and a commitment to Te Tiriti o Waitangi have been relentless in the policyscape over the last 12-18 months. Looking back at the past two editorials in Teachers’ Work, we critiqued the progressing privatisation and commercialisation of education (Couch et al., 2024), and the ongoing attempts of the current government to undermine Te Tiriti o Waitangi as a foundational document of our government and society (Jones et al., 2024). As Alwyn Poole opines in The Post (Poole, 2025), our education system appears to be in decline on multiple levels and none of the recent successive governments have made any substantial inroads that would address key issues, such as “an overworked and under-appreciated teaching profession; a general over-reliance on market-driven policy; a culture of testing, measurement and accountability; ongoing equity and access issues; and a lack of urgency in preparing students for the 21st century” (Baker, 2023, p. 14). Although one can argue that much has changed in recent years, these issues remain or indeed are being exacerbated.